Effect of plastic deformation on the optical and electrical properties in Cd0.96Zn0.04Te single crystals. (January 2017) - Lmai, F.; Moubah, R.; Amiri, A.El.; Boudali, A.; Hlil, E.K.; Lassri, H.
Abstract: Using UV–visible, photoluminescence, electrical measurements and ab -initio calculations, we study the effect of introduced dislocations on the optical and electrical properties in Cd0.96 Zn0.04 Te crystals. To generate dislocations, a plastic deformation on the Cd(111) and Te ( 1 ¯ 1 ¯ 1 ¯ ) faces was induced. It is shown that the plastic deformation results in: i) a decrease in Zn concentration in the deformed regions, which is higher on the Cd face, ii) decrease in the band gap energy, iii) an increase of acceptor concentration, and iv) the leakage current is higher on the Te face. Calculation of barrier height has led to identify the dominant defect, which is the complex Cd vacancies, acceptor center [ V Cd, A Cd ] on the Cd face and V Te on the Te side, respectively. Electronic structure calculations based on full potential linearized augmented plane waves (FPLAPW) method were performed as well and have shown that the optical band gap energy decrease upon deformation can be understood by the decrease in Zn content in the deformed regions. Highlights: The optical and electrical properties of undeformed and deformed CdZnTe crystals were studied. The deformation induces a decrease in the band gap energy ( Eg ). The dominant induced defects are found to be the complex (Cd vacancies, acceptor center) on the Cd face and V Te on the Te side. Ab -initio calculations have supported that the decrease in Eg is due to the decrease in Zn content in the deformed regions.